2006
DOI: 10.1002/polb.20748
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on miscibility and phase behavior of linear and star poly(2‐methyl‐2‐oxazoline) blends with poly(vinylidene fluoride)

Abstract: The comparative studies on the miscibility and phase behavior between the blends of linear and star‐shaped poly(2‐methyl‐2‐oxazoline) with poly(vinylidene fluoride) (PVDF) were carried out in this work. The linear poly(2‐methyl‐2‐oxazoline) was synthesized by the ring opening polymerization of 2‐methyl‐2‐oxazoline in the presence of methyl p‐toluenesulfonate (MeOTs) whereas the star‐shaped poly(2‐methyl‐2‐oxazoline) was synthesized with octa(3‐iodopropyl) polyhedral oligomeric silsesquioxane [(IC3H6)8Si8O12, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 66 publications
(102 reference statements)
0
7
0
Order By: Relevance
“…They found that linear/star blends are more miscible than the corresponding linear/linear blends, and linear/star mixtures are less miscible than star/star blends. Shen et al found that the star poly(2‐methyl‐2‐oxazoline) (POMx) was miscible with poly(vinylidene fluoride) (PVDF), but the blends of linear POMx with PVDF were phase‐separated. In our work, star‐shaped SBS 411 has wider free volume distribution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They found that linear/star blends are more miscible than the corresponding linear/linear blends, and linear/star mixtures are less miscible than star/star blends. Shen et al found that the star poly(2‐methyl‐2‐oxazoline) (POMx) was miscible with poly(vinylidene fluoride) (PVDF), but the blends of linear POMx with PVDF were phase‐separated. In our work, star‐shaped SBS 411 has wider free volume distribution (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this paper, we report the surprising enhancements in both the pore sizes and long-range order of mesoporous phenolic resins when templated by PEO-b-PCL diblock copolymers blended with star PEO octa-functionalized polyhedral oligomeric silsesquioxanes (PEO-POSS) as the homopolymer. We chose to use star PEO-POSS as the homopolymer because its degree of hydrogen bonding with phenolic resin is greater than those of linear homopolymers; 44,45 we anticipated that stronger intermolecular interactions might enhance the longrange order of the mesoporous structures. 46 With aging, we expected the cage-like POSS species to form larger silica clusters that can be also found in the walls of mesoporous silica.…”
Section: Introductionmentioning
confidence: 99%
“…Four‐arm star polymers with poly (2‐methyl‐2‐oxazoline) and poly(2‐ethyl‐2‐oxazoline) arms were prepared using tetrakis(bromomethyl)ethylene as the initiator 21. For the preparation of poly(2‐methyl‐2‐oxazoline) stars with well‐defined but fewer arms, either halomethylated silsesquioxane with eight initiating species in one molecule22, 23 or hexakis[p‐(bromomethyl) phenoxycyclotriphosphazene] can be used as initiators 24. Iron and ruthenium tris(bipyridine) complexes have also been employed as the macroinitiators for the polymerization of 2‐R‐2‐oxazoline monomers, where R = ethyl, methyl, phenyl or undecyl 25–28.…”
Section: Introductionmentioning
confidence: 99%